The role of human capital and institutions in economic growth: An approach to the case of Mexico - Quispe Aruquipa, Saul Roberto; Martínez Chapa, Oshiel (Acta Universitaria, 2022)
The Mexican economy has been characterized by its lower levels of growth in recent years; therefore, it is necessary to carry out an evaluation of the determinants suggested by the new literature on economic growth. Using a vector error correction (VEC) model, a long-term function of the determinants of growth, as measured by the real gross domestic product (GDP) per capita, was estimated. Based on a neoclassical production function, extended with variables such as human capital (measured by formal education) and institutions (measured by the legal system and property rights), the results suggest that these variables have a positive effect in the long term. The study concludes on the need for rethinking the economic policy, focusing fundamentally on promoting the relevant variables selected in this research.